Prevalence and associated factors of depression and anxiety in adolescents residing in Malay-operated non-government-run sheltered homes in Selangor, Malaysia - Mukhtar, Firdaus; Ding, Wai Eng; Lye, Munn Sann; Awang, Hamidin; Munawar, Khadeeja (Universiti Putra Malaysia Press, 2021)
This study aimed to determine the prevalence of depression, anxiety, and the associated factors among 632 adolescents (age range: 13-17 years, Mage = 14.47, SD = 1.32) staying in sheltered homes in Malaysia. The Malay versions of the Beck Depression Inventory, Beck Anxiety Inventory, Automatic Thoughts Questionnaire, and Rosenberg Self-Esteem Scale were applied. The overall prevalence of mild to severe depression and anxiety in this study was 70.9% and 82.3% respectively, with 64.1% for comorbidity of both symptoms. Specifically, the prevalence rates of minimal, mild, moderate, and severe depressive symptoms were 29.1%, 38.4%, 22.4%, and 10.1% respectively whereas the prevalence rates of minimal, mild, moderate, and severe anxiety symptoms were 17.7%, 27.7%, 33.2%, and 21.4% respectively. The severity of negative automatic thoughts increased with the severity of depression and anxiety. Age, anxiety, negative automatic thoughts, and self-esteem were significantly associated with depression while depression, negative automatic thought, and anger were significantly associated with anxiety. The high rates of depression and anxiety among adolescents residing in the sheltered homes indicate the need to identify these at-risk populations and provide trained personnel who can deliver psychiatric and psychological services at sheltered homes.